2018
DOI: 10.1039/c8ra01454j
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of tetracycline on biochar derived from rice straw and swine manure

Abstract: Comparing the adsorption ability of biochar from swine manure and rice straw on tetracycline and investigating the relative mechanisms involved in the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(49 citation statements)
references
References 49 publications
3
42
1
Order By: Relevance
“…Tang et al 6 and Jang et al 4 reported Freundlich as the best-fitted isotherm model for multilayer TC adsorption onto biochars produced from municipal sewage sludge and P. taeda. Similar to the previous literatures, 6 , 16 the DEAF-BC also possessed the 1/ n f value (0.702) less than 1 in the Freundlich model, indicating surface heterogeneity (see the Supporting Data ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Tang et al 6 and Jang et al 4 reported Freundlich as the best-fitted isotherm model for multilayer TC adsorption onto biochars produced from municipal sewage sludge and P. taeda. Similar to the previous literatures, 6 , 16 the DEAF-BC also possessed the 1/ n f value (0.702) less than 1 in the Freundlich model, indicating surface heterogeneity (see the Supporting Data ).…”
Section: Resultssupporting
confidence: 87%
“… 2 , 4 , 13 , 18 Since these interactions rely on the surface area of BC, the raw BCs from various feedstocks with limited surface areas provided low TC adsorption ( Table 1 ). 4 , 16 , 17 , 19 In contrast, the chemically and thermally activated BCs did show high adsorption of TC owing to their well-developed pore structures and high surface area ( Table 1 ). 4 , 13 , 14 , 17 , 20 However, the use of activated biochar would suffer from high costs associated with high consumption of chemicals and energy for the production of activated biochar.…”
Section: Introductionmentioning
confidence: 99%
“…where, q t and q e (mmol g À1 ) are the amount of antibiotics adsorbed at time t (h) and equilibrium; k 1 (h À1 ) and k 2 (g mmol À1 h À1 ) are the observed rate constants of the pseudo-rstorder and pseudo-second-order, respectively; k i (mmol h 0.5 g À1 ) is intra-particle diffusion rate constant; C is the intercept reecting the extent of the boundary layer thickness. 18 Freundlich, Langmuir and Temkin isotherm models were utilized to depict the adsorption performance.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 At high pyrolysis temperature, C]O can be broken down and produced byproduct gas or liquid, so the peak near 1600 cm À1 decreased. 51 The peak at 1400 cm À1 may be associated with the carboxylate C]O stretching. 52 The new peak appears near 1150 is corresponded to the C-O group when the pyrolysis temperature ranged from 500 to 700 C. 53 With the increase in temperature, the functional groups gradually weakened and partly disappeared, which proved that biochar had better adsorption at low temperature.…”
Section: Fourier Transform Infrared (Ft-ir) Analysismentioning
confidence: 99%